PERBEDAAN PENGARUH MEDIA AUDIO-VISUAL TERHADAP HASIL BELAJAR DI KELOMPOK TINGGI, SEDANG, DAN RENDAH PADA MATERI PERISTIWA ALAM - Nursetiati, Defri Andani; Panjaitan, Regina Lichteria; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
This research is based on the idea that instructional media is needed in the classroom learning as a tool to facilitate in conveying the subject that is considered as quite complex. One of the media that can be used in learning is audio-visual media.This study aims to determine the effect of audio-visual media on students' learning results of volcanic nature event of high, medium and low groups. This study used pre-experimental research with one group pretest-posttest design. The population in this study is all fifth grade students of SD all Lemahabang subdistrict in Cirebon regency. The sample of this research is the fifth grade students of SDN I Asem and SDN III Lemahabang with all students from both schools grouped into high, medium, and low group based on the results of natural science basic ability test. The research data obtained from the test of students’ learning result of volcanic natural event subject while students' response obtained from questionnaire given after learning and posttest take place. Data analysis has been done shows that: (1) Audio-visual media give positive effect to the improvement of student learning outcomes in high, medium and low group. (2) Learning using audio-visual media does not show a different positive effect on increasing learning outcomes between high, medium and low groups. (3) Most students’ respond positively to learning by using audio-visual media.This research is based on the idea that instructional media is needed in the classroom learningas a tool to facilitate in conveying the subject that is considered as quite complex. One of the media that can be used in learning is audio-visual media.This study aims to determine the effect of audio-visual media on students' learning results of volcanic nature event of high, medium and low groups. This study used pre-experimental research with one group pretest-posttest design. The population in this study is all fifth grade students of SD all Lemahabang subdistrict in Cirebon regency. The sample of this research is the fifth grade students of SDN I Asem and SDN III Lemahabang with all students from both schools grouped into high, medium, and low group based on the results of natural science basic ability test. The research data obtained from the test of students’ learning result of volcanic natural event subject while students' response obtained from questionnaire given after learning and posttest take place. Data analysis has been done shows that: (1) Audio-visual media give positive effect to the improvement of student learning outcomes in high, medium and low group. (2) Learning using audio-visual media does not show a different positive effect on increasing learning outcomes between high, medium and low groups. (3) Most students’ respond positively to learning by using audio-visual media.